Резонансні режими поширення нелінійних хвильових полів у середовищах з коливними включеннями - Даниленко, В.А.; Скуратівський, С.І. (Видавничий дім "Академперіодика" НАН України, 2008)
Using the asymptotic methods of nonlinear mechanics, the peculiarities of unifrequency resonance regimes of the spreading of nonlinear wave fields in a bounded rod are investigated within a mathematical model of media with oscillating inclusions.